ANALISIS FAKTOR INTERNAL PERUSAHAAN DAN PENGARUHNYA TERHADAP EXPECTED RETURN SAHAM - Natrion; Yusup Agus (Jurnal Satya Mandiri Manajemen dan Bisnis, 2015)
Corporate performance, constituting planning and operation tool for chairman of and investor in given time period. Investor that invest its fund on securities, really interested to current gain and expected gain at proximately and marks sense stability of gain who will be gotten. Before invests its fund investor do analysis to Ability Corporation to result gain. Investor decision always been regarded by risk zoom (risk) and return one that is expected (Return Expected), and gets procurement Return Expected maximal with zoom runs the risk that minimal. This research intent for description and analysing is profitability and Market Price BUMN that listed at Indonesian Stock Exchange. Corporate profitability and Market Price BUMN that listed at Indonesian Stock Exchange to be measured of Return on Assets, Return on Equity, dividend Payout Ratio, Earning per Share, Price Earning Ratio, Full scale Assets Turn Over, and Net Profit is Margin simultaneously having for significant to expected return stock. Profitability BUMN that listed at Indonesian Stock Exchange partially influential significant to expected return stock. Factor which of Return on Assets, Return on Equity, dividend Payout Ratio, Earning per Share, Price Earning Ratio, Full scale Assets Turn Over, and Net Profit Is Margin one that ascendant dominant to expected return stock. Base analysis result points out that profitability and Marker Price BUMN that listed at Indonesian Stock Exchange to be measured of Return on Assets, simultaneously ala having for significant to expected return stock. Corporate profitability and market price BUMN that listed at Indonesian Stock Exchange to be measured of dividend Payout Ratio and Net Profit is Margin partially influential significant to expected return stock. Meanwhile Return on Assets, Return on Equity, Earning per Share, Price Earning Ratio, and Full scale Assets Turn Over partially don't significant ascendant to expected return stock. Net Profit is Margin constituting corporate internal factor BUMN that listed at influential Indonesian Stock Exchange dominant to expected return stock.